Determinan Kualitas Implementasi Simda dan Implikasinya Terhadap Kualitas LKPD di Pemerintah Daerah Provinsi Jambi - Enggar Diah Puspa Arum; Ilham Wahyudi (Jurnal Akuntansi & Keuangan Unja, 2018)
The purpose of this research is to analyze determinants of SIMDA implementation quality and its implication on LKPD of Jambi Provincial Government quality. Determinants of SIMDA implementation quality in this research are user’s competence and information technology. Survey in this study is applied on 30 OPD of Jambi Provincial Government by using Partial Least Square analysis. The result indicates that user’s competence and information technology have significant positive effect to the quality of SIMDA implementation and furthermore the quality of SIMDA implementation has an effect to the quality of LKPD of Jambi Provincial Government. Keywords : Users competence, information technology, implementation of SIMDA, LKPD quality.